2018
DOI: 10.1007/s10278-018-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Andriod Device-Based Cervical Cancer Screening for Resource-Poor Settings

Abstract: Visual inspection with acetic acid (VIA) is an effective, affordable and simple test for cervical cancer screening in resource-poor settings. But considerable expertise is needed to differentiate cancerous lesions from normal lesions, which is lacking in developing countries. Many studies have attempted automation of cervical cancer detection from cervix images acquired during the VIA process. These studies used images acquired through colposcopy or cervicography. However, colposcopy is expensive and hence is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Although the next step in the use of smartphones in cervical cancer screening is the use of deep learning and AI algorithms to allow instant results, 39 these are not yet approved for routine clinical application. The very clear current potential application of smartphone image capture of the cervix is the capacity to transmit the basic image of the cervix after application of acetic acid or Lugol's iodine without the addition of any AI to a colposcopic expert remote from the woman and the health care worker undertaking the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the next step in the use of smartphones in cervical cancer screening is the use of deep learning and AI algorithms to allow instant results, 39 these are not yet approved for routine clinical application. The very clear current potential application of smartphone image capture of the cervix is the capacity to transmit the basic image of the cervix after application of acetic acid or Lugol's iodine without the addition of any AI to a colposcopic expert remote from the woman and the health care worker undertaking the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A study of smartphone cervicography with an inbuilt decision application evaluated the accuracy reported for high sensitivity and specificity. 22 Furthermore, studies of cervicography that evaluated this form of digital photography as an alternative to colposcopy suggested that it is a promising alternative method. 8,9 With the development of deep learning and automated visual evaluation of cervical images taken by a contemporary smartphone camera, using automated visual evaluation on smartphones could be useful in VIA for cervical cancer screening in low-and middle-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…Another drawback may be that the healthcare personnel performing the technique may not be experienced enough to distinguish VIA positive from VIA negative patients. Recently in a study by Kudva et al ( 65 ) an Android Device based screening method was proposed to address this issue. The novel technique suggests that during VIA examination the health care provider uses a speculum with an Android device attached to acquire images of the cervix prior to and after acetic acid application, as well as the patient's identification details.…”
Section: Recent Developments In Screening Methodsmentioning
confidence: 99%
“…Upon acquisition, these images are sent to a medical expert in the field, who after examination deems them VIA positive or negative. In a clinical study involving more than 100 women in India, it was found that the algorithm offered a sensitivity of 99.05% and a specificity of 97.16% ( 65 ).…”
Section: Recent Developments In Screening Methodsmentioning
confidence: 99%